Similarities and differences in the characteristics of the epidemical process tick-borne encephalitis and Lyme borreliosis - L. V. Rubis; O. V. Ekimova; О. S. Safonova; V. Е. Chevskaya (Журнал инфектологии, 2023)
Objective: To identify common and distinctive characteristics of the epidemical process of tick-borne encephalitis and Lyme borreliosis on the example of the Republic of Karelia.Materials and methods. The frequency of infected tick bites, dynamics, intensity, territorial, gender, age and social features of the incidence of tick-borne encephalitis and Lyme borreliosis in 2000–2021 were analyzed according to official statistics, epidemiological examination of foci and laboratory studies. The results of studies of 2379 blood samples of adults who were not ill and not vaccinated against tick-borne encephalitis for the presence of antibodies to the virus were analyzed.Results. The virulence of ticks in 2000–2021 decreased from 23.6 to 1.3%, infection with borrelia at the level of 13.4– 38.4%. The average long-term incidence rates of tick-borne encephalitis and Lyme borreliosis were 6.2 and 6.6 per 100 thousand, the dynamics of incidence had an average pronounced downward trend, correlated with the dynamics of requests for medical care of the population affected by ticks. The main clinical form of tick–borne encephalitis is meningeal (48%). Non-erythemic forms of borreliosis in recent years amounted to 39.1%. Antibodies of class G to tick-borne encephalitis virus were detected in 11.8±0.7% of the examined individuals. The territory of risk of infection with tick-borne encephalitis and Lyme borreliosis is the central and eastern part of the south of the Republic, where I.persulcatus dominates. The proportion of urban residents among patients with both infections is higher, but the incidence of urban and rural populations did not have significant differences. The incidence rates of tick-borne borreliosis in persons aged 40-49, 50-59 and 60 years and older are 1.6-2.2 times higher than those of tick-borne encephalitis, but the difference is not significant. At working age, the percent of men is higher than women, there are no differences among the elderly.Conclusions: Similar and different features of the epidemic process of tick-borne encephalitis and tick-borne borreliosis have been identified, which should be taken to improving the detection of diseases, predicting the situation and planning preventive measures.